Cholinergic Elicitation Prevents Ventricular Remodeling via Alleviations of Myocardial Mitochondrial Injury Linked to Inflammation in Ischemia-Induced Chronic Heart Failure Rats - Yang Zhao; Huaxin Sun; Kai Li; Luxiang Shang; Xiaoyan Liang; Hang Yang; Zhenyu Dong; Jiasuoer Xiaokereti; Shuai Shang; Qina Zhou; Xianhui Zhou; Ling Zhang; et al. (Mediators of Inflammation)
Background. Cholinergic anti-inflammatory pathway (CAP) is implicated in cardioprotection in chronic heart failure (CHF) by downregulating inflammation response. Mitochondrial injuries play an important role in ventricular remodeling of the CHF process. Herein, we aim to investigate whether CAP elicitation prevents ventricular remodeling in CHF by protecting myocardial mitochondrial injuries and its underlying mechanisms. Methods and Results. CHF models were established by ligation of anterior descending artery for 5 weeks. Postoperative survival rats were assigned into 5 groups: the sham group (sham, n=10), CHF group (CHF, n=11), Vag group (CHF+vagotomy, n=10), PNU group (CHF+PNU-282987 for 4 weeks, n=11), and Vag+PNU group (CHF+vagotomy+PNU-282987 for 4 weeks, n=10). The antiventricular remodeling effect of cholinergic elicitation was evaluated in vivo, and H9C2 cells were selected for the TNF-α gradient stimulation experiment in vitro. In vivo, CAP agitated by PNU-282987 alleviated the left ventricular dysfunction and inhibited the energy metabolism remodeling. Further, cholinergic elicitation increased myocardium ATP levels and reduced systemic inflammation. CAP induction alleviates macrophage infiltration and cardiac fibrosis, of which the effect is counteracted by vagotomy. Myocardial mitochondrial injuries were ameliorated by CAP activation, including the reserved ultrastructural integrity, declining ROS overload, reduced myocardial apoptosis, and enhanced mitochondrial fusion. In vitro, TNF-α intervention significantly exacerbated the mitochondrial damage in H9C2 cells. Conclusion. CAP elicitation effectively improves ischemic ventricular remodeling by suppressing systemic and cardiac inflammatory response, attenuating cardiac fibrosis and potentially alleviating the mitochondrial dysfunction linked to hyperinflammation reaction.